2021
DOI: 10.1038/s41467-021-26572-6
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent BRAF inhibition in advanced BRAF mutated melanoma results of a phase II randomized trial

Abstract: Combination treatment with BRAF (BRAFi) plus MEK inhibitors (MEKi) has demonstrated survival benefit in patients with advanced melanoma harboring activating BRAF mutations. Previous preclinical studies suggested that an intermittent dosing of these drugs could delay the emergence of resistance. Contrary to expectations, the first published phase 2 randomized study comparing continuous versus intermittent schedule of dabrafenib (BRAFi) plus trametinib (MEKi) demonstrated a detrimental effect of the “on−off” sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…Samples were further analyzed through the Personalis DNA pipeline for small variant calling (SNVs, InDels) and copy number changes. We used Qiagen Ingenuity Variant Analysis (IVA) [ 52 ] and QCI-I Translational platform [ 53 ] for variant calling. Variants filtering was done based on call quality, and allele frequency in known populations using 1000 Genomes Project [ 54 , 55 ], allele frequency community (including gnomAD and CGI), ExAC, and NHLBI ESP [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…Samples were further analyzed through the Personalis DNA pipeline for small variant calling (SNVs, InDels) and copy number changes. We used Qiagen Ingenuity Variant Analysis (IVA) [ 52 ] and QCI-I Translational platform [ 53 ] for variant calling. Variants filtering was done based on call quality, and allele frequency in known populations using 1000 Genomes Project [ 54 , 55 ], allele frequency community (including gnomAD and CGI), ExAC, and NHLBI ESP [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…So far, intermittent treatment of melanoma has been unproven, with clinical outcomes arguing for and against its potential effectiveness. On one hand, two recent phase II trials revealed worse progression-free survival in patients with melanoma treated intermittently with dabrafenib + trametinib or vemurafenib + cobimetinib compared with those treated with continuous therapy, with no difference in overall survival ( 38 , 39 ). On the other hand, retrospective and prospective studies of dozens of patients who progress on BRAF or MEK inhibitor have reported that more than one-third show a second clinical response after a drug holiday period ( 27 , 33 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical reports and a phase 2 clinical trial have shown dozens of cases where patients with melanoma develop resistance and progress when treated with BRAF or MEK1/2 inhibitors continuously, but then show further response when retreated after a drug holiday period ( 32 37 ). By contrast, phase 2 trials of intermittent dosing with BRAF and MEK inhibitor combinations showed worse progression-free survival and no difference in overall survival compared with continuous treatment ( 38 , 39 ). The reasons for variability in patient responses and trial outcomes are unknown and may reflect an incomplete understanding of mechanisms underlying the response to intermittent treatment.…”
mentioning
confidence: 94%
“…To date, no routine biomarkers have been approved to determine early response in patients with metastatic melanoma treated with BRAF-MEK inhibitors. Some studies have shown that the serial determination of the BRAF mutation in circulating tumour DNA (ctDNA) can help predict the response to treatments for patients with melanoma [ 23 , 24 , 25 ], but this technique has very limited implementation. In addition, studies have been undertaken to carry out genomic analyses to predict survival or treatment response in mutated BRAF melanoma, but these studies all used tumour tissue and, in most cases, few samples were taken, due to the risks involved in rebiopsy, among other considerations [ 26 ].…”
Section: Discussionmentioning
confidence: 99%